Identification of pulsating flow effects with CNT nanoparticles on the performance enhancements of thermoelectric generator (TEG) module in renewable energy applications - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In this study, performance assessment of a thermoelectric generator module located in between two channels where carbon-nanotube/water nanofluid streams flow is studied with combined effects of nanoparticle inclusion and flow pulsations. The finite element method is used to solve the 3D unsteady coupled fluid flow, heat transfer and electric field equations. Different pertinent parameters effects such as Reynolds number (between 250 and 1000), nanoparticle volume fraction (between 0 and 0.04), pulsating flow frequency (Strouhal number between 0.01 and 0.1) and amplitude (between 0.25 and 0.95) on the power generation are examined. It is observed that flow pulsation changes the dynamic features of thermoelectric power generated in the device. Higher power values are obtained when Reynolds number, flow pulsation amplitude and nanoparticle solid volume fraction rise. However, the effect is reverse for higher pulsation frequencies. Including nano sized particles further enhances the performance of the device with flow pulsation. It is also observed that 24.4% enhancement in the power are achieved for nanofluid with flow pulsation when lowest and highest pulsation amplitudes are compared. At lowest pulsation frequency and highest amplitude 14.2% enhancement in power is ob-tained for water as compared to steady flow case while this amount rises to 31% for carbon nanotube nanofluid at the highest solid volume fraction. System identification method is used to obtain dynamic lower order model of the system for different pulsation amplitudes to predict the time dependent power generated in the thermoelectric generator device. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: thermoelectric energy; Finite element method; CNT-Nanofluid; Pulsating flow